Co-Targeting Tumor Angiogenesis and Immunosuppressive Tumor Microenvironment: A Perspective in Ethnopharmacology - Zhou, Jianbo; Wang, Li; Peng, Cheng; Peng, Fu (Frontiers in Pharmacology, 2022)
Tumor angiogenesis is one of the important processes of cancer deterioration via nurturing immunosuppressive tumorenvironment (TME). Targeting tumor angiogenesis has been widely accepted as a cancer intervention approach, which is also synergistically associated with immune therapy. However, drug resistance is the biggest challenge of anti-angiogenesis therapy, which affects the outcomes of antiangiogeneic agents, and even combined with immunotherapy. Here, emerging targets and representative candidate molecules from ethnopharmacology (including traditional Chinese medicine, TCM) have been focused, and they have been proved to regulate tumor angiogenesis. Further investigations in derivatives and delivery systems of these molecules provide a comprehensive landscape in preclinical studies. More importantly, the molecules library of ethnopharmacology meets the viability for targeting angiogenesis and TME simultaneously, which is attributed the pleiotropy of pro-angiogenic factors (such as VEGF) towards cancer cell, endothelial cells, immune cells etc. We primarily shed a sight on the potentiality of ethnopharmacology against tumor angiogenesis, particularly TCM. The more researches concerning the crosstalk between angiogenesis and TME remodeling from the perspective of botanical medicine are awaited.